Biodiesel production from wastewater scum of dairy industry: Lipid extraction studies and reaction routes. (15th June 2023) - Abreu-Jaureguí, C.; Reynel-Ávila, H.E.; Bonilla-Petriciolet, A.
Graphical abstract: Highlights: Lipids from residual dairy effluents are a low-cost feedstock to obtain biodiesel. Solvent extraction using ethyl butyrate achieved 72% of sewage scum lipid recovery. Valorization of dairy scum waste via thermal and solvent extraction was analyzed. Taguchi experimental design was used to improve the FAME formation. Abstract: This study focused on the extraction of lipids from sewage scum of dairy effluents and their subsequent conversion to biodiesel. Thermal- and solvent-based liquid extraction processes were compared under different conditions. Kinetic studies of lipid extraction were performed using hexane, ethyl acetate, propionate, and butyrate at 25–50 °C. The results showed that solvent-based extraction outperformed the thermal-based extraction method, achieving a lipid recovery of 71.9% using ethyl butyrate at 50 °C for 1 h. The experimental data from the extraction studies were modeled using first- and second-order extraction models, and the best fit was obtained using the former model. Two reaction routes were analyzed and compared to obtain biodiesel from the lipids extracted from sewage scum. The best reaction conditions were identified by applying the Taguchi experimental design. It was found that the esterification/transesterification of scum lipids was the best alternative to obtain 94% FAME formation. This study contributes new findings to valorize the biomass generated from the dairy industry to obtain biodiesel and, therefore, consolidate its supply chain in urban areas worldwide.